Penerapan Arsitektur Neo Vernakular Pada Perancangan Sport Academy di Sumatera Utara - Reza, Muhammad; Saraswaty, Rina (Universitas Medan Area, 2024)
Sports in the country, especially in North Sumatra, still need special attention from leaders to find new talents and improve the achievements of athletes. Sport is part of social activity, its existence is no longer underestimated, sport is part of community activity. Sport is a form of refinement of Indonesian society that builds character and character, or discipline and sportsmanship, and produces achievements that increase national pride.... The purpose of this paper is to design a Sport Academy in Deli Sport City, North Sumatra by using the Neo Vernacular Architecture Approach Concept. The design focuses on the theme that has been determined and is included in the form and supporting facilities in the Sport Academy building. The results of this writing study can provide conclusions in designing the Sport Academy requires the form and application of themes in the design that can add visual value, so that it becomes an attraction for people to learn and hone their skills at the Sport Academy.